Design of a New Step-like Frame FBAR for Suppression of Spurious Resonances - Kumar, Puneet; Tripathi, Chandra Charu (Společnost pro radioelektronické inženýrství, 2013)
Film bulk acoustic wave resonators (FBARs) are of great interest for wireless applications due to its inherent advantages at microwave frequencies. However, the presence of spurious modes near the main resonance degrades the performance of resonators and requires development of new methods to suppress such unwanted modes. Different techniques are used to suppress these spurious modes. In this paper, we present design of a new step-like frame structure film bulk acoustic wave resonator operating near 1.5 GHz. The simulated results are compared with simple frame-like structure. The spurious resonances are eliminated effectively and smooth pass band is obtained with effective coupling coefficient of 5.68% and quality factor of 1800. The equivalent electrical mBVD model of the FBAR based on impedance response is also presented. These highly smooth phase response and passband skirt steepness resonators are most demanding for the design of low cost, small size and high performance filters, duplexers and oscillators for wireless systems.
Keywords: Film Bulk Acoustic Wave Resonator; step-like frame; spurious resonance; effective coupling coefficient; COMSOL Multiphysics